An assessment of the effects and influences of the concept of entrepreneurial learning in Serbia - Marija N. Marčetić; Gordana T. Prlinčević; Biljana Grujić Vučkovski (Anali Ekonomskog fakulteta u Subotici, 2020)
It is difficult to estimate the quantity and quality of the necessary entrepreneurial knowledge and assess the effects of such entrepreneurship education, i.e. whether it has met the set criteria sufficiently. Empirical practice lacks empirical studies that would base the competences of entrepreneurial learning upon the direct assessment of learning outcomes, the outcomes related to the knowledge of opportunities for professional orientation and the knowledge of the business environment, the created framework picture of entrepreneurship, employment opportunities and obstacles. In this paper, the direct effect of entrepreneurial learning in a secondary-education and a higher-education institution of the economic path was estimated through a qualitative approach, after the established conceptual framework and furthermore through the respondents’ answers to the survey questions. Therefore, a contribution was made by making a step forward in the evaluation of entrepreneurial learning through a direct assessment of the raised awareness of entrepreneurship. The indirect indicators used were the gender and the education level, i.e. the difference in the respondents’ answers according to their respective gender and the school they are attending (secondary school or vocational school). The obtained results assess the level of the respondents’ basic entrepreneurial culture and their knowledge, as well as entrepreneurial preferences.